(untitled) (World Bulletin of Management and Law, 2022)
This article talks about raising the legal consciousness and legal culture of youth as a factor of social stability. Legal culture is an integral part of the legal values of the nations of the world. In world practice, legal culture is characterized by the realization of a person’s duty and responsibility to society, and the realization of a sense of respect for the law